Meat Consumption and sustainability: Attitudes in Spanish younger generations - Rodríguez Cánovas, Belén; Guzmán Rincón, Alfredo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Spain is the first European country in meat consumption. Meat consumption and it effects are frequently discussed in different areas due to the negative impact on environment and human health. Therefore, society needs to increase the awareness to reconsider meat consumption. This study explores Spanish younger generation attitudes towards meat consumption. Results evidence that they are worried about the negative effects of meat consumption but some barriers are highlighted. For example, the lack of information prevents them from modifying their meat consumption habits.